Analysis of Nuclear Mitochondrial DNA Segments of Nine Plant Species: Size, Distribution, and Insertion Loci - Young-Joon Ko; Sangsoo Kim (Genomics & Informatics)
Nuclear mitochondrial DNA segment (Numt) insertion describes a well-known phenomenon of mitochondrial DNA transfer into a eukaryotic nuclear genome. However, it has not been well understood, especially in plants. Numt insertion patterns vary from species to species in different kingdoms. In this study, the patterns were surveyed in nine plant species, and we found some tip-offs. First, when the mitochondrial genome size is relatively large, the portion of the longer Numt is also larger than the short one. Second, the whole genome duplication event increases the ratio of the shorter Numt portion in the size distribution. Third, Numt insertions are enriched in exon regions. This analysis may be helpful for understanding plant evolution.